Development and validation of the Hospitality Axiological Scale for Humanization of Nursing Care - José María Galán González-Serna; Soledad Ferreras-Mencia; Juan Manuel Arribas-Marín
ABSTRACT Objective: to develop and validate a scale to evaluate nursing attitudes in relation to hospitality for the humanization of nursing care. Participants: the sample consisted of 499 nursing professionals and undergraduate students of the final two years of the Bachelor of Science in Nursing program. Method: the instrument has been developed and validated to evaluate the ethical values related to hospitality using a methodological approach. Subsequently, a model was developed to measure the dimensions forming the construct hospitality. Results: the Axiological Hospitality Scale showed a high internal consistency, with Cronbach's Alpha=0.901. The validation of the measuring instrument was performed using factorial, exploratory and confirmatory analysis techniques with high goodness of fit measures. Conclusions: the developed instrument showed an adequate validity and a high internal consistency. Based on the consistency of its psychometric properties, it is possible to affirm that the scale provides a reliable measurement of the hospitality. It was also possible to determine the dimensions or sources that embrace it: respect, responsibility, quality and transpersonal care.